Partial purification and characterization of anhydrotetracycline oxygenase of Streptomyces aureofaciens - Vancurová, I; Flieger, M; Volc, J; Benes, M J; Novotná, J; Neuzil, J; Bĕhal, V (Journal of basic microbiology, 1987)
Anhydrotetracycline oxygenase was purified both by affinity chromatography and by hydrophobic interaction chromatography. Molecular weight of anhydrotetracycline oxygenase was determined to be 115,000 by Sephadex G-200 gel filtration. Using preparative isoelectric focusing the isoelectric point of the enzyme was estimated to be 5.3. The enzyme showed a sensitivity to thiol-specific inhibitors. During the hydrophobic interaction purification step, the activity dropped considerably. Reactivation occurred when a heat treated crude extract was added to the reaction mixture.
Keywords: Isoelectric Focusing; isoelektrická fokusace; gelová chromatografie; Oxygenases; Streptomyces aureofaciens; molekulová hmotnost; Chromatography, Gel; Molecular Weight; oxygenasy; chromatografie afinitní; izoelektrický bod; Isoelectric Point; Chromatography, Affinity